PROFITABILITAS, STRUKTUR MODAL DAN LIKUIDITAS PENGARUHNYA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN REAL ESTATE YANG LISTED DI BEI TAHUN 2012-2015 - Amalia Nur Chasanah; Daniel Kartika Adhi (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2017)
PBV shows how far a company is able to create a company's value relative to the amount of capital invested. The higher the PBV ratio can be interpreted the more successful the company creates value for shareholders. The aim of this study to test Profitability, Capital Structure and Liquidity of its effect on Corporate Value on Listed Real Estate company in BEI Year 2012-2015. The sample used in this study is real estate companies listed on the Stock Exchange in 2012-2015 as many as 40 companies, so the number of samples 160. Data analysis techniques used are multiple regression with classical assumptions multicollinearity, autocorrelation, heteroskedastisitas and normality. The results showed that ROA and DER variables have a significant positive effect on PBV. While the CR variable has no significant negative effect on PBV. Adjusted r square value of 0.206 which means that the variable ROA, CR and DER able to explain the PBV of 20.6%.